Introduction to the Thematic Section on STEM Education - Radakovic, Nenad (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación, 2025)
This introduction frames the thematic section on STEM education by questioning what becomes visible and invisible when learning is organized through disciplinary lenses. Drawing on the author’s experiences as a mathematics educator and on place-based pedagogical examples, it situates STEM education within broader social, ecological, and ethical contexts. The introduction outlines the contributions of the articles in the section, which engage Deweyan democratic traditions, decolonial and Indigenous perspectives, embodied and outdoor pedagogies, and speculative futures. Collectively, the section advances a vision of STEM education that is transdisciplinary, community-oriented, and responsive to historical, cultural, and environmental relations.